2003
DOI: 10.1161/01.atv.0000083342.98342.22
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypertension on Early Carotid Artery Remodeling

Abstract: Objectives-We aimed to analyze the influence of hypertension on early large artery remodeling. Methods and Results-Carotid intima-media thickness (IMT) and diameter were measured ultrasonographically in 394 normotensive subjects and 327 untreated and 528 treated hypertensive patients. IMT and diameter were increased in hypertensive groups, treated or untreated, compared with the normotensive group (PϽ0.001). Positive association existed between diameter and IMT in the overall study population (PϽ0.001), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 17 publications
10
45
0
2
Order By: Relevance
“…37,38 In the current study, the carotid IMTlumen diameter relationship was significantly stronger in hypertensives than in normotensives, suggesting a synergistic influence of blood pressure and arterial thickening on lumen enlargement. This observation is consistent with the finding from a previous study 39 and supports the concepts mentioned.…”
Section: Ruan Et Al Correlates Of Carotid Artery Diameter 705supporting
confidence: 94%
“…37,38 In the current study, the carotid IMTlumen diameter relationship was significantly stronger in hypertensives than in normotensives, suggesting a synergistic influence of blood pressure and arterial thickening on lumen enlargement. This observation is consistent with the finding from a previous study 39 and supports the concepts mentioned.…”
Section: Ruan Et Al Correlates Of Carotid Artery Diameter 705supporting
confidence: 94%
“…Other studies, which were restricted to the CCA, yielded confl icting results. While some studies showed that the common carotid lumen was reduced ( 15 ), did not vary across categories of US-assessed IMT ( 3,16,17 ), or remained stable until an IMT threshold was reached ( 18,19 ), others actually showed overcompensation (larger lumens with greater IMT) ( 6,(20)(21)(22).…”
Section: Neuroradiology: Remodeling Of the Carotid Arteriesmentioning
confidence: 99%
“…10,13,18,23 Plaque was detected by high-resolution ultrasound (ATL 5000; Philips), using a probe with an operating frequency of 5 to 12 MHz for carotid and femoral investigations and of 5 MHz for abdominal aorta, and defined as a focalized encroachment into lumen by Ͼ1.5 mm. Each of the 3 sites investigated was characterized either by the absence of any plaque, or by the presence of at least 1 plaque regardless the number and location of such plaques.…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%